(untitled) (World Bulletin of Public Health, 2022)
The researcher’s purpose in doing this study is to investigate Iraq’s environment and the level of pollution in the country It also investigates the negative effects of pollution on human health, such as air, water, soil, food, auditory, and visual pollution, which rapidly affects human health through disease. Understanding Iraq’s environmental problems and pollution through investigating the many causes of environmental deterioration in Iraq